2020
DOI: 10.1002/rth2.12442
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐13 and bleeding phenotype in von Willebrand disease

Abstract: Background The bleeding phenotype of von Willebrand disease (VWD) varies highly between patients and can only partly be explained by von Willebrand factor (VWF) parameters. By cleaving large VWF multimers into smaller, less active multimers, ADAMTS‐13 is an important regulator of VWF activity. However, it is unknown what the role of ADAMTS‐13 is in individuals with VWD. Objectives We therefore studied how ADAMTS‐13 activity is associated with the laboratory and bleeding phenotype in individuals with VWD. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Intriguingly, we found that type 2A patients with A2 mutations had high PF4 levels, which might indicate a similar interaction in vivo . We did not find an association between ADAMTS13 activity and PF4 levels (data not shown), but the assay for ADAMTS13 activity is not suited to determine how PF4 affects ADAMTS13‐mediated VWF proteolysis 15 . Thus, our data cannot decisively answer if PF4 plays a role in VWF interactions and ADAMTS13‐mediated proteolysis in vivo yet, but suggests this could ultimately be relevant to type 2A patients.…”
Section: Discussionmentioning
confidence: 71%
“…Intriguingly, we found that type 2A patients with A2 mutations had high PF4 levels, which might indicate a similar interaction in vivo . We did not find an association between ADAMTS13 activity and PF4 levels (data not shown), but the assay for ADAMTS13 activity is not suited to determine how PF4 affects ADAMTS13‐mediated VWF proteolysis 15 . Thus, our data cannot decisively answer if PF4 plays a role in VWF interactions and ADAMTS13‐mediated proteolysis in vivo yet, but suggests this could ultimately be relevant to type 2A patients.…”
Section: Discussionmentioning
confidence: 71%
“…This cleavage is mediated by ADAMTS 13 [14]. ADAMTS 13 binds and cleaves cell-bound UL-VWF strings at the Tyr 1605 -Met 1606 bond, thereby eliminating the UL-VWF from the endothelial surface and resulting in the fragmentation of the VWF strings, to prevent VWF-induced platelet over-aggregation and thrombosis, thus playing a role in maintaining clotting homeostasis [15]. The mutation of VWF protein at amino acid 1606 in patient 2 may impact the ADAMTS13 cleavage site, which results in an increase in the amount of UL-VWF strings, leading to coagulation dysfunction.…”
Section: Discussionmentioning
confidence: 99%